Report : Proposed new interior design of Art Centre at NO 49, 49A & 49B, Jalan Plumbum Q 7/Q Seksyen 7 ,40 000 Shah Alam Selangor Darul Ehsan for small talk with the moon / Nurul Nabihah Zainol - Zainol, Nurul Nabihah (Faculty of Architecture, Planning and Surveying, 2012)
All final year student of Diploma Interior Architecture are required to completed every stage of their final design. This is to analysis towards student’s knowledges about interior design from basic to the final presentation in board. Propose new interior design of Art Center at No 49, 49A & 49B Jalan Plumbum Q 7/Q, Seksyen 7 Shah Alam for Small Talk With The Moon, has been chosen for this final project. This is because, the client would like to move from the previous site to a better place. Besides that, it also to introduce about Small Talk With The Moon art center to the market. The concept and image that used for this art center must be reflect with client’s needed and the theme of the Small Talk With The Moon. Furthermore, through interviews, observation, media, internet and case study can be used to finish this project.